New requirements for technical acceptability of construction products as a component of the construction quality assurance system - Lytvynenko , O. (Ways to Improve Construction Efficiency, 2021)
The analysis and generalization of theoretical approaches to the formation of the construction quality system, the generalization of the legislative and regulatory framework for quality control in construction. Analysis of the theoretical prerequisites for the formation of quality control of construction revealed that the digital transformation of construction is an integral part of the development of modern society, a prerequisite for changing the system of construction, including control, quality assurance and evaluation of construction processes, works, materials, products and structures. It was found that the quality in construction is directly affected by the following factors: quality and completeness of design documentation; the possibility and obligation to comply with legal requirements; quality of construction processes and works, strict compliance with the requirements of technology and construction organization; quality of construction products and structures; technical ability to provide a given level of quality with the help of machines, mechanisms, means of small mechanization, etc .; the level of qualification of management staff, workers and line ITP. The quality system itself can be presented in the format of a "black box", where the factor will be named at the entrance, and at the exit - buildings and structures that meet a given level of quality throughout the life cycle of the object. It is proposed to consider the construction quality management system in the form of a multicomponent formation and at the same time a dynamic environment, which is constantly changing under the influence of external and internal factors and has a high degree of scholasticism and uncertainty. With the introduction of digital technologies in the organization of construction, including VIM modeling, use of artificial intelligence, cloud services for information storage, quality control tools that can be performed without human intervention, such as drones, robotic elements, surveillance cameras and others, the construction quality assurance system has to change, taking into account the realities of time. Therefore, the system of quality formation in the article is proposed to be considered throughout the life cycle of the object - from pre-project research to liquidation. This will, in contrast to existing approaches, not only combine into a single system all the components of assurance, evaluation and quality control, which are used at the level of all participants in the construction, but also to ensure integrated process management.